IMPROVEMENT STUDENT COOPERATION USING COOPERATIVE LEARNING MODELS OF NUMBERED HEADS TOGETHER (NHT) TYPE ON VIII GRADE STUDENTS OF SMP MUHAMMADIYAH 2 MINGGIR SLEMAN - Andri Wijaya; Suparyan Suparyan (AdMathEduSt: Jurnal Ilmiah Mahasiswa Pendidikan Matematika, 2017)
Cooperation of students while following the process of mathematics is still lacking. Using a cooperative learning model with the type of NHT expected to improve cooperation of students in particular on VIII grade student of SMP Muhammadiyah 2 Minggir Sleman in odd semester of the academic year 2015/2016. The purpose of this study is to improve cooperation students in learning mathematics using a cooperative learning model with the type of NHT VIII grade of students SMP Muhammadiyah 2 Minggir Sleman in odd semester of the academic year of 2015/2016. The research is classroom action research. The subject of the is VIII grade students of SMP Muhammadiyah 2Minggir Sleman in odd semester of an academic year of 2015/2016. The object of the research is the cooperation improvement of student's mathematics in learning to use the cooperative learning model with the type of NHT. The study is done in two cycles. Data were collected by using observation sheets, interview sheets and daily tests which had reviewed by supervising lecturer, mathematics teachers, and had been validated by the lecturer expert. An analysis of the data is used was descriptive analysis qualitative. The result showed that the cooperative learning model with the type of NHT can improve the cooperation of students in grade VIII of SMP Muhammadiyah 2 Minggir Sleman in odd semester of the academic year 2015/2016. This comes from the observation of student's cooperation on each cycle that had been increased, namely the percentage of student's cooperation cycle I worth 57,29% with criteria of enough, and in cycle II increase to 71 % with the criteria of good.